Rigorous dap in the early years : from theory to practice - Brown, Christopher Pierce; Feger, Beth Smith; Mowry, Brian Nelson (Redleaf Press, 2018)
The RIGOROUS DAP construct is composed of two parts: academic rigor and developmentally appropriate practices. Teachers who engage in RIGOROUS DAP recognize there is no single way to educate children. Instead, they create the conditions for all children to learn at high levels by providing them with multiple learning opportunities to gain the knowledge and skills needed for success in and out of school.